Legal Consequences for Debtors Due to Failure to Remove Fiduciary Guarantees - Rachmawati, Miranti Ayu; Haliwela, Nancy Silvana; Sinaga, Roulinta Yesvery (Faculty of Law, Universitas Pattimura, 2026)
Introduction: The issue of the non-deletion of fiduciary security remains a matter that continues to be overlooked. In many cases, the deletion is not carried out by the fiduciary recipient, their representative, or attorney after the termination of the principal agreement. This situation causes harm to the fiduciary grantor, even though the loss may not be felt directly. One of the consequences is that when the fiduciary grantor applies for a loan from a financial institution, the application may be rejected because the collateral object is still recorded as active in the fiduciary registry.Purposes of the Research: To identify and analyze the factors behind the non-deletion of fiduciary security and the legal consequences for the fiduciary grantor if the fiduciary security is not deleted.Methods of the Research: The research method used is normative legal research with a statutory approach and case approach. The sources of legal materials used include primary legal materials, secondary legal materials, and tertiary legal materials. The technique for collecting legal materials is carried out through literature study using a qualitative method, along with limited interviews as supporting field data to strengthen the normative analysis.Findings of the Research: The research results show that the failure to delete fiduciary security by the fiduciary recipient is caused by their negligence and lack of awareness regarding the obligation to carry out the deletion. In addition, the absence of strict sanctions for failing to perform the deletion contributes to the issue. This situation causes harm to the public, resulting in disruptions to their economic activities. Therefore, there is a need for stricter regulations concerning the deletion process, and the Ministry of Law and Human Rights must continuously supervise these financing institutions.